2017
DOI: 10.4103/aer.aer_55_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of locally administered dexmedetomidine as adjuvant to levobupivacaine in supraclavicular brachial plexus block: Double-blind controlled study

Abstract: Context:Brachial plexus block is effective with good postoperative analgesia in upper limb surgery has gained importance as it safe, low cost, and maintains stable hemodynamics intraoperatively. To decrease the onset time and prolong the duration of nerve block bicarbonate, opioids (morphine, fentanyl, etc.), sympathomimetic agents (epinephrine, phenylephrine, etc.), α-2 agonists (clonidine and dexmedetomidine), calcium channel blocker (verapamil), magnesium sulfate, etc., were studied with local anesthetics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Similar to our findings, previous two randomized double-blinded trials by Bisui et al and Kaur et al and a meta-analysis done by Abdallah and Brull showed that the addition of dexmedetomidine to local anesthetic in the brachial plexus block was reported to shorten the onset time of the sensory block [ 15 - 17 ]. Adinarayanan et al used a control group with the dexmedetomidine and dexamethasone groups [ 18 ], whereas Singh et al compared dexmedetomidine and dexamethasone in the brachial plexus block under ultrasound guidance [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, previous two randomized double-blinded trials by Bisui et al and Kaur et al and a meta-analysis done by Abdallah and Brull showed that the addition of dexmedetomidine to local anesthetic in the brachial plexus block was reported to shorten the onset time of the sensory block [ 15 - 17 ]. Adinarayanan et al used a control group with the dexmedetomidine and dexamethasone groups [ 18 ], whereas Singh et al compared dexmedetomidine and dexamethasone in the brachial plexus block under ultrasound guidance [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Across all included studies, a total of 3332 patients were assessed. DEX was used as an adjuvant to several different local anesthetics, which included ropivacaine [ 23 , 34 , 39 , 41 , 42 , 45 47 , 49 , 50 , 52 , 56 , 57 , 59 , 63 66 , 68 , 72 – 74 , 76 , 78 , 80 , 81 , 84 , 85 ], bupivacaine [ 20 , 35 , 37 , 38 , 40 , 51 , 53 55 , 67 , 69 , 71 ], levobupivacaine [ 21 , 43 , 44 , 48 , 60 62 , 79 , 83 ], and lidocaine [ 22 , 36 , 70 , 77 , 86 ]. Across the studies, the dose of DEX ranged from 0.5 μg/kg to a total of 150 μg.…”
Section: Resultsmentioning
confidence: 99%
“…In 161 studies, patients received a supraclavicular brachial plexus block, 26,29–160 in 40 studies, patients received an axillary brachial plexus block, 24,27,161–198 in 28 studies, an interscalene block was performed, 25,199–220 in 11 studies, patients received an infraclavicular brachial plexus block, 221–231 one study used a coracoid approach to brachial plexus block 232 and one study used a suprascapular combined with axillary nerve block 233 . A detailed description of included studies is presented in the supplemental content (supplemental table 3, http://links.lww.com/EJA/A839).…”
Section: Resultsmentioning
confidence: 99%